Desarrollar El Proceso De Atención de Enfermería En Paciente De 32 Años Embarazada Con Diagnostico De Preeclampsia - Navarro Sudario, América Geraldine (2019)
This clinical case is based on a disease that can occur in pregnant women; preeclampsia is a pathology that appears in the first months of pregnancy, is characterized by hypertension and high protein values in the urine (proteinuria), one of the factors that lead to this problem are: family history, autoimmune diseases, age, the lack of knowledge and the little care and interest in attending routine medical check-ups, this is why there is a very high rate of cases of pregnant women with preeclampsia nationwide, since this is one of the most serious complications, in where not only the life of the mother is at risk but also that of the fetus. This pathology is classified as two mild stages in which care must be taken, but the values are not as high, as in the severe one where blood pressure can reach 160/100 and above, with this it can trigger Another much more serious problem is eclampsia where the patient may suffer from seizures and other signs and symptoms of greater complexity. The only form of prevention would be for mothers to perform the necessary prenatal controls during pregnancy so that the doctor can diagnose, control and offer proper treatment; With this the pregnant woman may have a normal pregnancy.